The most common viral lesions in the genital area encountered by gynecologists in everyday practice - Rotsztejn, Helena; Zalewska, Anna; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
The aim of the study is to familiarize gynecologists with a very important problem of viral diseases located in the genital region, because of potential carcinoma risk, possibility of intrauterine infections in pregnant women and consequences for the newborn. The most commonly encountered viral infections of the genital region in women have been reviewed, including condylomata acuminatum, herpes genitalis, molluscum contagiosum and herpes zoster.